2011
DOI: 10.1096/fj.10-161497
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing replication and osteogenesis of aged mesenchymal stem cells by exposure to a young extracellular matrix

Abstract: This study aimed to determine whether aging negatively affects MSC replication and osteogenesis and whether these features could be altered by exposure to an extracellular matrix (ECM) generated by marrow cells from young or old mice. A cell-free ECM was prepared from cultured femoral marrow cells from either 3- or 18-mo-old C57BL/6 mice (young-ECM or old-ECM, respectively). The replication and osteogenesis of young or old MSCs maintained on young-ECM vs. old-ECM as well as plastic were examined in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
145
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(159 citation statements)
references
References 39 publications
9
145
2
1
Order By: Relevance
“…[23][24][25]28,37 To further mimic an in vivo situation, we took this technology to the next level by developing a 3D tissue-specific scaffold and investigated its effect on the proliferation and differentiation capacity of MSCs. Such 3D scaffolds coated with a native ECM synthesized by bone marrow stromal cells exhibited a biomimetic bonemarrow-like microenvironment (or ''niche'') in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25]28,37 To further mimic an in vivo situation, we took this technology to the next level by developing a 3D tissue-specific scaffold and investigated its effect on the proliferation and differentiation capacity of MSCs. Such 3D scaffolds coated with a native ECM synthesized by bone marrow stromal cells exhibited a biomimetic bonemarrow-like microenvironment (or ''niche'') in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] To further mimic an in vivo situation, a 3D stem cell culture system that represents the physiological architecture of the bone marrow tissue may offer new insights on MSC function. Researchers utilize a variety of scaffolds to study the behavior of MSCs in 3D cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the data regarding ADSC regenerative potential were obtained from cells delivered from relatively healthy young donors; however, it was known that aging and disease itself may negatively affect MSC activities [21][22][23][24][25][26], including proliferation and differentiation potential [27][28][29][30] as well as angiogenic properties [29,31]. Because MSCs are considered to be components of the vessel wall and take part in its reparation after injury, their cellular modification due to aging can be an important pathogenic factor of agerelated diseases such as atherosclerosis, diabetes, and arterial hypertension [32].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that certain culture conditions, including the use of specific atmospheric conditions and culture substrates, exert positive effects on not only the proliferation rate, but also the extent of proliferation. For instance, low oxygen condition, suitable extracellular matrix (ECM), small molecules compounds have been applied to stimulate the proliferation of stem cells in vitro [19][20][21]. Low oxygen condition largely mimics normal physiological condition of tissues.…”
Section: Stem Cell Proliferation In Vitromentioning
confidence: 99%